Associations of menopausal age with virological outcomes and engagement in care among women living with HIV in the UK. Issue 6 (22nd November 2020) - Okhai, Hajra; Tariq, Shema; Burns, Fiona; Gilleece, Yvonne; Dhairyawan, Rageshri; Hill, Teresa; Sabin, Caroline A.
Abstract : Background: Women ageing with HIV undergo sex-specific changes. There is limited evidence available with regards to how the menopause impacts HIV outcomes. Objective: To investigate whether menopausal age is associated with engagement-in-care (EIC), viral load (VL) suppression and rebound among women living with HIV. Methods: Women were grouped by age (<40, 40–50, >50 years), corresponding to pre-, peri- and post-menopausal stages. EIC, HIV VL suppression (VL < 50 copies/mL) within 12 months of antiretroviral therapy initiation and VL rebound (two consecutive VL > 50 copies/mL) after VL suppression were compared across age groups using logistic/Cox proportional hazards regression. Associations were compared to those seen in heterosexual men. Results: Six thousand four hundred and fifty-five (6455) eligible women (median age 36 [interquartile range: 29–42], 64.4% black African, 19.1% white) contributed 44, 226 person-years (PYRS) of follow-up; 29, 846, 10, 980 and 3, 399 PYRS in those aged <40, 40–50 and >50, respectively. Women were engaged-in-care for 79.5% of follow-up time, 3, 344 (78.0%) experienced VL suppression and 739 (22.1%) VL rebound. After adjustment, women aged >50 years had lower EIC than those aged <40. Women aged 40–50 were more likely to have VL suppression and were less likely to experience VL rebound than those aged <40 years. Trends in heterosexual men were similar for EIC but with no evidence of a higher VL suppression rate in those aged 40–50 years ( p int.  0< .0001) and a stronger protective association between older age and VL rebound ( p int.  0< .0001). Conclusion: Our findings warrant further research into the potential impact of the menopause to support women and clinicians through HIV care.